Perfil de egreso maestría de Salud Pública mención Enfermería Familiar y Comunitaria: una propuesta desde el análisis documental - María José, Escobar Erazo (2021)
ABSTRACT The objective of this research work was to determine the elements required by the national postgraduate commission of the Council for Quality Assurance in Higher Education (CACES) in the Master of Public Health in Family and Community Nursing. Thus, the professional must develop intellectual and attitudinal skills to help solve the health problems of a community by providing services of promotion, prevention, treatment, and rehabilitation. To achieve this goal an extensive knowledge to develop guidelines, protocols among others, are necessary. The graduates need to find solutions not only to the present problems but also in the future. They need to guide the epidemiological data for which the master must be a leader and guide not only in the health team but also the population. Bibliographic research was conducted to identify these characteristics by collecting national and international scientific information published in indexed pages such as Pubmed, E-book, Scielo, MedLine, Lilacs, Proquest, Scopus, and other official sites such as World Health Organization (WHO), Pan American Health Organization (PAHO), Ministry of Public Health (MOH), journal articles and world reports. It was concluded that the graduates' profile requires an advanced level of study, which integrates science, technology, and practice. Upon completing their studies, the master should have developed critical thinking that helps to examine the needs and problems in the health system. Furthermore, establishing priorities and providing solutions more critically, respecting the rights and interculturality that each person has to build trust between the health team and the community. Thus, helping to improve the quality of life of the population and becoming a professional leader. Keywords: Profile of Graduation, Public Health, Family, Community. Reviewed by: Dr. Narcisa Fuertes, PhD. ENGLISH PROFESSOR cc: 1002091161